2015
DOI: 10.1111/ijpp.12172
|View full text |Cite
|
Sign up to set email alerts
|

Reducing unacceptable missed doses: pharmacy assistant-supported medicine administration

Abstract: PA-supported medication rounds can significantly reduce the rate of omitted doses. This study provides evidence for a potential solution to the problem of omitted doses for hospital inpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 11 publications
3
18
1
1
Order By: Relevance
“…The pilot randomised trial of TECHMED to determine impact on omitted dose outcomes revealed that the service was associated with a similar predicted probability of a total or 'preventable' omitted dose occurring when compared to existing practice at the study hospital either during the 'active service' or 'post-intervention' periods and when compared with 'pre-implementation'. This is in contrast with indications from an earlier study of a similar service involving pharmacy assistants that it may be effective in reducing 'unacceptable' omitted doses, [12] but our study is not directly comparable as we evaluated a pharmacy technician-led service in a different hospital using a larger dataset with process evaluation. The inclusion of process evaluation interviews was important in interpreting the RCT findings by revealing the reality of service implementation and delivery for stakeholders.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…The pilot randomised trial of TECHMED to determine impact on omitted dose outcomes revealed that the service was associated with a similar predicted probability of a total or 'preventable' omitted dose occurring when compared to existing practice at the study hospital either during the 'active service' or 'post-intervention' periods and when compared with 'pre-implementation'. This is in contrast with indications from an earlier study of a similar service involving pharmacy assistants that it may be effective in reducing 'unacceptable' omitted doses, [12] but our study is not directly comparable as we evaluated a pharmacy technician-led service in a different hospital using a larger dataset with process evaluation. The inclusion of process evaluation interviews was important in interpreting the RCT findings by revealing the reality of service implementation and delivery for stakeholders.…”
Section: Discussioncontrasting
confidence: 75%
“…This is important as interest in the concept of greater involvement of pharmacy teams in medicines administration continues to grow in the United Kingdom. [12,25,26] Process evaluation participants gave indications that a targeted approach focusing on particular medication rounds and wards where omitted doses may be more prevalent, as well as utilising pharmacy technicians on wards which they are most familiar with may help to optimize benefits of the service and maximise efficient use of limited resources. Targeting limited resources to areas of most need aligns with recent efficiency recommendations in the sector made by Lord Carter of Coles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These omission data are lower than omission rates from previous research studies, which estimate that 80% of patients have an omitted dose [32]. This variance is may be due to a number of factors such as whether studies measure the rate of omissions of doses, or the rate of patients with omitted doses [33]. Other reasons include: studies examining different drug classes or whether data are collected from electronic prescribing and administration systems, which have the potential to impact omissions and identifying the rate of omissions [34].…”
Section: Lessons Learnedmentioning
confidence: 94%